New restaurants and their intra-industry effects: evidence from Portugal - Luís Miguel Serra Coelho (Tourism & Management Studies)
This paper investigates the intra-industry effects resulting from the birth of a new restaurant at Portugal. Using event-study methods, this paper finds that, in the year the new competitors open for business, industry rivals experience an average abnormal loss of -17.6% in their return-on-assets, which is due to a significant decrease in their profit margin, and asset turnover ratio. Regression analysis further shows that high industry concentration, low labor productivity, and low asset profitability magnify the rivals’ underperformance, which is particularly acute when the restaurants are located at Lisbon and Oporto, the two most heavily populated Portuguese cities. Overall, this paper contributes to the literature studying the economics of the eating-places industry, and has important implications for both practice, and public policy